2020
DOI: 10.1001/jamahealthforum.2020.1318
|View full text |Cite
|
Sign up to set email alerts
|

Drug Overdose Deaths Head Toward Record Number in 2020, CDC Warns

Abstract: Even as the rising number of US coronavirus disease 2019 (COVID-19) deaths dominates the spotlight, another national public health crisis-overdose deaths from use of illicit drugs-shows no sign of abating. An estimated 19 416 individuals died of a drug overdose in the United States in the first 3 months of 2020 compared with 16 682 in the same 3-month period in 2019, according to preliminary data released last week by the US Centers for Disease Control and Prevention's (CDC's) National Center for Health Statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 0 publications
0
38
0
Order By: Relevance
“…Data from the National EMS Information System (NEMSIS) show that overdose-related cardiac arrests have risen sharply [3]. Provisional data from the US Centers for Disease Control and Prevention indicates that overdose deaths are on pace to reach a new all-time high in 2020 [4].…”
Section: Introductionmentioning
confidence: 99%
“…Data from the National EMS Information System (NEMSIS) show that overdose-related cardiac arrests have risen sharply [3]. Provisional data from the US Centers for Disease Control and Prevention indicates that overdose deaths are on pace to reach a new all-time high in 2020 [4].…”
Section: Introductionmentioning
confidence: 99%
“…A recent report published by the Centers for Disease Control and Prevention (CDC) reported that approximately 81,230 drug overdose deaths occurred in the United States between June 2019 and May 2020, which is the largest number of drug overdoses for a 12-month period ever recorded (2). The increases in drug overdose deaths appear to have accelerated during the COVID-19 pandemic (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Data from the National EMS Information System (NEMSIS) show that overdose-related cardiac arrests have risen sharply (3). Provisional data from the US Centers for Disease Control and Prevention indicates that overdose deaths are on pace to reach a new all-time high in 2020 (4).…”
Section: Introductionmentioning
confidence: 99%